Propagation of Eichhornia Crassipes and its Water Purification Properties in Poultry Farm Waters (Texas Journal of Agriculture and Biological Sciences, 2022)
This article describes the results of scientific research conducted in Khorezm region to study the reproduction of Eichhornia crassipes and its water purification properties in the wastewater of poultry enterprises.